Social media-based online brand community characteristics’ impact on consumer relationship formation: The moderating effects of platform initiator types - Gubalane, Alona; Ha, Yongsoo (International Journal of Innovative Research and Scientific Studies, 2025)
This research investigates the impact of online brand community characteristics on social media. Information quality, system quality, virtual interactivity, and rewards are modeled as key indicators examining their effects on two types of consumer relationships: consumer-brand and consumer-other-consumer relationships. This research further explores how these consumer relationships influence community identification and electronic word-of-mouth communication. Additionally, it examines the moderating effects of platform initiator types such as firm-initiated and consumer-initiated brand communities on the link between consumer relationships and community identification. A quantitative study was conducted using an online questionnaire distributed through Amazon Mechanical Turk, and data were analyzed using structural equation modeling. The findings indicate that forming social media-based online brand community characteristics as a latent construct is significantly influenced by information quality, system quality, virtual interactivity and rewards. These characteristics have a notable impact on both types of consumer relationships significantly influencing community identification and electronic word-of-mouth. Test results have also shown that the moderating effects of platform initiator types are significant only in the relationship between the consumer-other-consumer relationship and community identification. In firm-initiated brand communities, consumer-other-consumer relationships significantly influence community identification whereas in consumer-initiated brand communities, this relationship was not significant. Therefore, marketers are encouraged to establish branding strategies that align with the nature of the community to cultivate and sustain consumer relationships.